Modelling and seasonal forecasting of monthly hotel nights in Denmark - Nils Karl Sørensen (European Regional Science Association (ERSA), 2002)
The paper examines the monthly forecasting performance of several models of hotel demand in Denmark by nationality. Statistics are covering a period of more than 30 years, and special attention is devoted to the role of seasonality. Deterministic as well as stochastic seasonality is considered. The data generating process is also examined from a more traditional view by estimating an ECM-model where hotel demand is assumed to depend on economic variables like the foreign and Danish CPI and the exchange rate and variables measuring the climate.
Keywords: 330